Epidemiology of HPV in HIV-Positive and HIV-Negative Fertile Women in Cameroon, West Africa. (24th January 2009) - Desruisseau, Andrew J.; Schmidt-Grimminger, Delf; Welty, Edith
Abstract : Background . HPV types vary by country and HIV status. There are no data on the prevalent HPV genotypes from Cameroon. Methods . We conducted a cross-sectional, observational study on 65 Cameroonian women. Samples were sent for HPV genotyping and Thin Prep analyses. Results . 41 out of 61 samples tested (67.2%) had HPV subtypes detected. The most common high risk types encountered were: 45 (24.6%) and 58 (21.5%). HIV-positive women were more likely to test positive for any HPV (P = .014 ), have more than one HPV subtype (P = .003 ), and to test positive for the high risk subtypes (P = .007 ). Of those with high risk HPV, HIV-positive women were more likely to have Thin Prep abnormalities than HIV-negative women (P = .013 ). Conclusions . Oncogenic HPV subtypes 45 and 58 were more prevalent than those subtypes carried in the quadrivalent vaccine. Further studies are needed to assess whether the current vaccine will be effective in this region.